Optimization of energy efficiency work surfaces with environment by creating asymmetric surface-active structures (including squamose-like) with the vector direction given resistance - Горенко, М.В. (Problems of Tribology, 2016)
The paper first proposed to optimize the working surface energy exchange with the environment using calculated for given conditions asymmetric elements with a given surface portions vector resistance, particularly squamose-like structural elements that unite into localization and groups, the general vector resistance given relative to the surface. The variants structures and the possibility of their creation on contact surfaces of a given profile based on a base object roughness to improve the efficiency and effectiveness tribosystems. We give a general definition of efficiency structured surface. This method of increasing the efficiency of working surfaces, equipment for its implementation is proposed for introduction and use in production.